Drilling and Blasting in Hot and Reactive Ground Conditions at Barrick Goldstrike's Meikle Mine - Remi Proulx; D. Scott Scovira (International Society of Explosives Engineers, 2000)
The Meikle Mine is a high grade, underground gold mine utilizing primary-secondary longhole open stoping with delayed backfill to produce 3000 stpd of ore. Hot and reactive ground conditions were encountered early on in the mine life. Ground temperatures up to 330” F were measured. In the early stages of mining, the mine experienced premature detonations using different explosives. The learning curve to safely mine this high-grade gold deposit in hot and severely reactive ground was indeed very steep. Currently, the Meikle Mine uses a special buffered bulk emulsion in all blasts to address hot and reactive ground concerns. In addition, exacting procedures are also followed to ensure safe work with explosives. The combination of new explosives technology and strict loading procedures permits high mine productivity with the highest degree of safety.